From classroom to clinic: A cross sectional survey on fostering awareness of biomedical waste management among the dental students - K. Nitya; P. Perumal; Baskaran Kumarasamy; Bhuvaneshwari Gangadharamurthy (Wolters Kluwer Medknow Publications, 2024)
Background: In dental practices, biomedical waste (BMW) management is essential to preserving a clean and safe atmosphere for patients and medical personnel. Dental facilities generate different forms of BMW, which include sharps, contaminated materials, and/or potentially infectious substances, which require proper handling, storage, and disposal to minimize the risk of infection and environmental contamination. Aim: The study aimed to assess the knowledge and awareness of BMW management among dental students in Chennai city using paper-based questionnaire. Materials and Methods: An observational cross-sectional survey containing 28 questions was framed to assess the knowledge and awareness of BMW management among the final-year BDS, interns, and postgraduate students (a total of 100 students). Statistical analysis was done using SPSS version 27.0. Results: The results of our study showed statistically significant results with P = 0.01 among the study groups. The overall knowledge, attitude, and practice score was observed to be 67.5% for final-year BDS students, 68.09% for interns, and 71.76% for postgraduates. Conclusion: The knowledge assessed was found to be average among the participants. Hence, proper training and assessment are necessary for the proper handling and practice of BMW management.